Survey Instrument Development for Consumer Perception Testing to RTE Product in Convenience Store - Dyah Lestari Widaningrum; Wiwit Amrinola; Fuadi Nasution (Bina Nusantara University, 2015)
Global trade and the abolition of trade barriers lead to the proliferation of imported food products such as various types of fast food products (RTE: ready-to-eat food) sold by convenience stores mainly scattered in Jakarta. The question is what causes consumers choose certain convenience store to buy RTE Product and not choose another outlet category. To understand consumer perceptions, it is necessary to develop an instrument for measuring consumer perceptions of the option to purchase RTE Product at convenience stores. Variables used in this research are the perception and knowledge of the public/consumers against food safety, store attributes, service, and product attributes. The instrument used in this study is a questionnaire with a scalemeasuring1-5 to see the relationship between variables, we used the method of Structural Equation Modeling (SEM). The sample used in this study was 223 respondents that were divided into five areas in Jakarta, namely Central Jakarta, West Jakarta, South Jakarta, East Jakarta, and North Jakarta. The final outcome of the instrument development process was 25 observed variables, consisting of 4 indicators, which valid and reliable, with T-values for each observed variable is above 2,58, and Construct Reliability values range between 0,76 to 0,853.